Workplace Predictors of Parenting Educators' Technology Acceptance Attitudes. (June 2017) - Walker, Susan K.; Hong, Seonghee
Abstract : The purpose of this study was to examine technology use by licensed parenting educators and to explore workplace conditions as influences on the educators' technology acceptance attitudes. The study adapted the Technology Acceptance Model (TAM) as a theoretical framework and proposed 10 hypotheses to be examined. Responses to an online survey ( N  = 279) indicated that information search and email were used most frequently. In contrast, social media and online learning platforms were infrequently used. Structural equation modeling revealed that technology attitudes were directly related to Perceived Ease of Use and Perceived Usefulness of technology. Also, Workplace Encouragement and Workplace Infrastructure indirectly influenced acceptance attitudes as mediated by Perceived Usefulness and Perceived Ease of Use, respectively. The results suggest that parenting educators' adoption of technology needs to be supported by a workplace culture that promotes and provides resources for technology use.